On-surface synthesis of planar acenes via regioselective aryl–aryl coupling. Issue 36 (1st April 2020) - Feng, Lin; Wang, Tao; Jia, Hongxing; Huang, Jianmin; Han, Dong; Zhang, Wenzhao; Ding, Honghe; Xu, Qian; Du, Pingwu; Zhu, Junfa
Abstract : The reaction of 2, 2′-dibromo-biphenyl (DBBP) on a Ag(111) surface leads to the generation of planar dibenzo[ e, l ]pyrene, in contrast to the nonplanar saddle-shaped tetraphenylene formed in solution. Abstract : The reaction of 2, 2′-dibromo-biphenyl on a Ag(111) surface leads to the formation of planar acenes with a high-regioselectivity rather than nonplanar saddle-shaped tetraphenylene as the typical product in solution chemistry. The regioselective aryl–aryl coupling reaction is attributed to the hydrogen repulsion between the reactants on the confined two-dimensional surface.